BRIDGING LEGACY AND MODERN: ARCHITECTURAL PATTERNS FOR ORACLE SOA SUITE INTEGRATION WITH CLOUD-NATIVE SPRING BOOT SERVICES - Nagireddy Vasipally, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article presents a comprehensive framework for integrating Oracle SOA Suite with Spring Boot microservices in cloud environments, addressing the challenges organizations face when modernizing their enterprise integration architectures. The article examines architectural patterns, security considerations, and implementation strategies for achieving seamless integration between traditional enterprise service bus implementations and cloud-native microservices. Through systematic analysis of service mediation patterns, data synchronization approaches, and DevOps practices, this article establishes a set of best practices for organizations undertaking digital transformation initiatives. The article demonstrates that successful integration requires a multi-faceted approach encompassing API management, security architecture, and performance optimization strategies. This article contributes to the body of knowledge in enterprise integration architecture by providing practitioners with concrete implementation patterns and recommendations for achieving scalable, secure, and maintainable hybrid cloud architectures.